2005
DOI: 10.1103/physrevb.71.165107
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-field effects in the mixed-valence compoundsYb2M3Ga9(M=

Abstract: Magnetic susceptibility, heat capacity, and electrical resistivity measurements have been carried out on single crystals of the intermediate valence compounds Yb2Rh3Ga9 and Yb2Ir3Ga9. These measurements reveal a large anisotropy due apparently to an interplay between crystalline electric field (CEF) and Kondo effects. The temperature dependence of magnetic susceptibility can be modelled using the Anderson impurity model including CEF within an approach based on the NonCrossing Approximation.PACS numbers: 75.30… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…From the Lorentzian fits it is possible to extract the static susceptibility. Good agreement (Table 1) is found at all temperatures, except at 12 K where it appears that the INS response is not sensitive to the low temperature upturn (which is probably extrinsic) observed in the static susceptibility [1]. This agreement gives confidence in our determination of S mag .…”
supporting
confidence: 67%
See 1 more Smart Citation
“…From the Lorentzian fits it is possible to extract the static susceptibility. Good agreement (Table 1) is found at all temperatures, except at 12 K where it appears that the INS response is not sensitive to the low temperature upturn (which is probably extrinsic) observed in the static susceptibility [1]. This agreement gives confidence in our determination of S mag .…”
supporting
confidence: 67%
“…Recently, we have established that Yb 2 Rh 3 Ga 9 is an anisotropic intermediate valence (IV) system [1,2]. In these studies, we found that Anderson impurity model (AIM) calculations, including the effects of crystal field (CF) level splitting, were able to simultaneously reproduce the temperature dependence of the magnetic susceptibility and the 12 K inelastic neutron scattering spectrum (INS).…”
mentioning
confidence: 98%
“…[21] Also a Kondo model has been solved exactly for particular parameters. [22] The non-crossing approximation (NCA), which has been successfully used to calculate thermodynamic properties of generalized Anderson models above or near the Kondo temperature T K , [23][24][25] has also been used for nonequilibrium situations. [26][27][28] Unfortunately, at low temperatures this method fails to fulfill Fermi liquid relations in the equilibrium case, [29] and the spectral density presents a spurious peak at the Fermi level in the presence of a magnetic field B.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these limitations related with lattice effects, our approach was successful to describe magnetic susceptibility and specific heat of Yb compounds in the non-magnetic phase [8,9]. We believe that it can also be used inside the magnetic phase, leading naturally to small magnetic moments as a consequence of the saturation of…”
mentioning
confidence: 86%
“…This points to a strong AF interaction 1 between the Yb ions. However, the system does not order due to the dominance of the single ion is necessary for a quantitative agreement with experiment [9]. Here we describe the general formalism.…”
mentioning
confidence: 96%